Strengthening Millet Value Chain through Farmer Producer Organizations - Sangappa,; Dudekula, Rafi; B.Laxmi,; E. Charishma,; K Srinivasa Babu, (Indian Journal of Extension Education, 2023)
Millets are a group of small-seeded “Nutri-Cereals” that are grown as food crops in many parts of the world and is need of hour for achieving nutritional security. In the traditional supply chain, millet farmers were not getting remunerative prices but being the members in Farmers' Producer Organizations, the share in the consumer rupee was increased. The value chain approach was used for analyzing the supply chain aspects of millets to strengthen the linkages, increase efficiency, competitiveness, and profitability. The study was conducted during 2022-23 with ICAR-IIMR promoting FPOs. The establishment of a primary processing unit by ICAR-IIMR at the FPO farm gate through the FPO strengthened the millet value chain by engaging FPOs/SHGs/rural women/unemployed youth in preparing value-added products and delivering them through the GeM portal, ONDC, FPO Bazar, and e-commerce platforms. To meet the millet value chain challenges overall adoption of improved technologies, better market linkages, and increased investment in infrastructure were the key strategies. Primary processing, value-added technology adoption by FPOs and declaring minimum support price by the state government, and creating facilities to procure at MSP by establishing millet food parks, millet shakti cafes, and millet bazar were found key sources to generate better income.